THE MOTHER TONGUE IN NATION-BUILDING: THE (UN)MAKING OF A POSTCOLONIAL NATION - Tupas, Ruanni (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2023)
Mother tongue, used as the language of instruction, is considered vital for effective pedagogy, individual rights recognition, and social justice. It offers marginalized students a more efficient pathway to learning compared to foreign or hegemonic national languages like English or Filipino. Mother Tongue-Based Multilingual Education (MTB-MLE) challenges systems favoring colonial languages and asserts the importance of children's first languages. However, the political and ideological dimensions of mother tongue are often overlooked, as it can be manipulated to serve specific agendas in nation-building efforts. While some analyze its linguistic aspects, this paper delves into its political nature, exploring how it intersects with ideologies shaping nation-building and potentially nation-destroying processes. This article asserts that the mother tongue serves not only as a learning tool but also as a contested political concept vital for envisioning inclusive nation-building. By examining MTB-MLE in the Philippines, it explores how the mother tongue influences nation-making, as well as reimagining and shaping national identities.